Analysis of Cipelang River Strorage Capacity Regency Sumedang - tribhuwana, awliya; Farhan, Ohan (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
Rainy season flooding: Ujung Jaya Regency experiences flooding almost every year, this annual flood phenomenon causes material losses. The research aims to analyze the capacity of the Cipelang River which is located in Sumedang Regency. The Cipelang River is part of the Cimanuk Watershed (DAS) with an area of ​​around 130.70 km², which has several tributaries such as Ciandana, Cicacaban, and Cipanassaat. The methods used in this research include collecting hydrological data, topographic analysis, and evaluating land use around the river. Rainfall and river flow data were taken from the nearest meteorological station to determine water storage potential. Results of analysis of existing river storage capacity and flood discharge. The maximum capacity of the Cipelang river is 409,002 m3/s. Nakayasu HSS method planned discharge using river watershed discharge occurs in the 100 year anniversary period. However, time periods of 2,5,10,25,50 years are considered safe. The results of comparing the planned discharge of the Hasper method with the discharge of the river catchment did not occur. So the most suitable method to use is the hasper method, land use which is dominated by irrigated rice fields and gardens also contributes to water management in this watershed. It is hoped that this research can provide recommendations for better water resource management and flood risk mitigation in the area. These findings are important to support sustainable infrastructure development and maintain ecosystem balance in the Sumedang Regency area. Keywords: Rain , River, Discharge, Capacity, Flood